Case Study: Pyothorax in Domestic Short Hair Cat - Hasanah, Nurmaulida; Mentari, Upakarti Dwi; Zaenab, Siti; Ichsanniyati, Zulfa (Veterinary Biomedical and Clinical Journal, 2022)
One of the diseases caused by pathogenic microbial infections is pyothorax. Pyothorax, also known as thoracic empyema, accumulates purulent exudates in the pleural space. This study aims to understand the diagnosis and therapy of pyothorax in Domestic Short Hair (DSH) cats. A male DSH cat came with a harsh breath condition or acute dyspnea. The cat was breathing more rapidly, having to make more effort to breathe. The anamnesis showed that the patient had a cough history and repeated with a dyspnea condition. Some diagnoses were radiographic examination (x-ray) and laboratory tests such as complete blood cell, blood chemistry, cytology, and bacterial culture. Result of radiography examination and laboratory examination showed that increasing of white blood cells or leukocytosis in complete blood cell test, fluid loss (dehydration) in the blood chemistry test, radiography (x-ray) imaging saw the abnormalities in the lungs that was a white color (radio-opaque) and looked homogeneous. Thoracocentesis founded pleural effusions in the form of pus/pyo, cytology examination found polymorphonuclear cells (PMN) neutrophils and mononuclear cells (MN), and the result of pus bacterial culture was Acinobacter baumannii. The examination results in patients showed positive pyothorax with causal of Acinobacter baumanii. Antibiotic therapy sensitive to Acinobacter baumanii had been proven effective until the patient recovered. The antibiotics for therapy started with 10 mg/kg BW of Enrofloxacin, 20 mg/kg BW of Meropenem, and 20 mg/kg BW of Tigecycline. Tigecycline has proven to be effective until the cat recovers.